Tinjauan Maqashid Syari’ah pada Jual Beli Diamond Game Online Mobile Legend Studi Kasus di Desa Kesilir Kec. Wuluhan Kab. Jember - Mahya Sa'idah, Irma; Khoirunnisa', Reza (SPT. haria Journal and Education Center Publishing, 2026)
With the advancement of technology, online buying and selling now encompasses more than just everyday necessities; it also includes transactions involving online game vouchers. One example is the sale of diamonds in the game Mobile Legends. In Indonesia, online gaming enthusiasts are quite numerous, including Mobile Legends, which is currently the most popular game in Indonesia. This study aims to determine the Islamic legal perspective on the sale and purchase of Mobile Legends game vouchers (diamonds). The data used are primary data, collected through documentation and interviews. Secondary data sources include documents, books, notes, and written works relevant to the research theme. The results of this study indicate that the sale and purchase of Mobile Legends game vouchers (diamonds) is similar to other online transactions in general. However, the object is a virtual object, namely currency that can be used in the game. From an Islamic legal perspective, this sale and purchase is considered valid because it meets the pillars and requirements of a sale and does not involve any elements of fraud.